Village-Based Waste Management System: The Study Case in Borobudur Sub-District, Indonesia - WAHYUNINGSIH, Siti; SUSILOWATI, Tuti; ASHAR, Hadi; PRIBADI, Avry; PRIBADI, Avry; SATYAJI, Teguh; SUKAMSI, Sukamsi; PURWATI, Purwati; ERNAWATI, Dhanik (Journal of Environmental Management and Tourism, 2024)
Waste problems are challenges for tourism areas, including the Borobudur sub-district. To mitigate these problems, the central government and state-owned enterprises built temporary landfills, or TPS 3R, in 12 of the 20 villages in the Borobudur sub-district. This study observes the TPS 3R's effectiveness in the Borobudur sub-district in reducing household waste unloading in a final landfill. The TPS 3R is the local government program to manage waste problems in residential areas. The Ministry of Public Works and Housing and state-owned enterprises built the TPS 3R in the Borobudur sub-district, which was then activated and operated by the village government. On one side, the TPS 3R burdens the village authorities and the environmental regulatory agency to manage and supervise the TPS 3R. Despite that, the involvement of some village authorities at the managerial level results in a financial burden for TPS 3R. TPS 3Rs are self-sufficient with less support from the local authorities, which affects the worker's welfare. Accordingly, the TPS 3R tends to raise the levy fee annually to cover daily activities. In addition, the absence of SOP and the managers' lack of experience in waste management resulted in some infrastructure being idled. However, the TPS 3R effectively minimizes household waste unloading to a final landfill. Structured abstract. This study aims to observe the effectiveness of TPS 3R as a village-based waste management system in the Borobudur sub-district in reducing the amount of municipal waste transported to a final landfill. We conducted the study in Borobudur sub-district, Indonesia, from 2022 to 2023, utilizing semi-structured interviews and focus group discussions. The interviewees consisted of managers and employees of TPS 3R and waste banks from twelve villages in the Borobudur sub-district, a head of the Borobudur sub-district, a head of the Environmental Agency, and a head of the Development Planning Agency. A focus group was held with Empowering Family Welfare members and health workers in the Borobudur sub-district. The data collected from the interview and focus group was then analyzed narratively. The TPS 3R was built by the Ministry of Public Works and Housing and state-owned enterprises on village land. The TPS 3R was equipped with infrastructure such as a biodigester, a compost shredder, and two garbage collection tricycles. The TPS 3R operates independently with less financial support from the local government, resulting in low welfare for the workers. Also, the largest type managed by TPS 3R is organic waste, which requires a longer time to compost but has a low selling price. Accordingly, TPS 3R revenue depends on the household levy fee. However, the levy fee tends to increase each year to cover the TPS 3R activities, which results in a decrease in customer numbers and threatens TPS 3R sustainability. On the other side, the involvement of some village authorities at the managerial level loads up the TPS 3R budget. Also, the on-site manager, a volunteer, manages the TPS 3R as usual, resulting in some infrastructure being idled. However, the TPS 3R reduces the amount of household waste dumped in a final landfill. Village-based waste management systems are not widely applied yet in Indonesia. As the Borobudur sub-district is one of the top tourist destinations, the central government built TPS 3R at the village level to overcome waste problems in the future.